The Problems on Implementation of Fuel Trade Act, B.E. 2543, in Maha Sarakham Province - Kaewtungkuen, Apiwat; Songklin, Prayote (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objective of research article were 1) to study the problems of the Fuel Trade Act, B.E. 2543, implementation in Maha Sarakham province, (2) to compare the problems of the Fuel Trade Act, B.E. 2543, implementation in the Maha Sarakham province between different sizes of fuel oil service stations, 3) to study suggestions for the problem solutions of the Fuel Trade Act, B.E. 2543, implementation in Maha Sarakham province. Sample group consisted of 175 people from fuel oil service stations in Maha Sarakham province. The interviewees were 10 people. Data in the study were collected by using a questionnaire and a structured-interview form. Data were analyzed using percentage, mean, standard deviation, and F-test (One-way ANOVA). The research study found as follows: 1. The overall opinion of the operators of the fuel oil service stations in Maha Sarakham province about the problems of the Fuel Trade Act, B.E. 2543, implementation in the province were at moderate level. When considering in each aspect, it was found that they were at medium levels in all aspects. 2. The operators of the fuel oil service stations in Maha Sarakham province that have difference sizes had different opinions concerning about the Fuel Trade Act, B.E. 2543, implementation, in overall. When considering in each aspect, it was found that the tools or operational equipment aspect was not different. On the other hand, the opinions were different in regulations - laws, personnel, coordination, and information aspects, statistically significant at .05 level. 3. The solution is that the agency should provide tools and equipment used in their operations which must be of quality, modern and sufficient. The staff from the relevant departments have integrated the work. There is an annual training or rehearsal of a joint action plan. Moreover, fuel stations should have regular quality and safety controls. There is a measure for the operator to provide tools and equipment for quality inspection at each service station.